2007
DOI: 10.1210/jc.2006-0857
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hyperparathyroidism and the Presence of Kidney Stones Are Associated with Different Haplotypes of the Calcium-Sensing Receptor

Abstract: Our data indicate that the CASR SRQ haplotype is significantly associated with PHPT in our population. Within the PHPT patient population, the AGQ haplotype is significantly associated with kidney stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 36 publications
3
63
0
5
Order By: Relevance
“…Therefore, common variants of the CASR gene modulate the effect of PTH-related hypercalcaemia on renal calcium handling ( Table 4). The 990G allele, located in the cytoplasmic tail of the receptor protein, has been associated with increased renal calcium excretion in PHPT Italian patients (78,79). Two further single nucleotide polymorphisms (SNPs), located in the regulatory region of the CASR gene, rs7652589 and rs1501899, are associated with kidney stones occurrence in PHPT patients (80).…”
Section: Calcium-sensing Receptor (Casr)mentioning
confidence: 99%
“…Therefore, common variants of the CASR gene modulate the effect of PTH-related hypercalcaemia on renal calcium handling ( Table 4). The 990G allele, located in the cytoplasmic tail of the receptor protein, has been associated with increased renal calcium excretion in PHPT Italian patients (78,79). Two further single nucleotide polymorphisms (SNPs), located in the regulatory region of the CASR gene, rs7652589 and rs1501899, are associated with kidney stones occurrence in PHPT patients (80).…”
Section: Calcium-sensing Receptor (Casr)mentioning
confidence: 99%
“…The frequency of the AR/AR haplotype was higher in this Chinese population, although the difference was not significant. By contrast, Scillitani et al (3) found that there was a lower frequency of the AR haplotype in Italian PHPT patients than in controls (66.7 vs 71.9%). The results suggest that the resulting amino acid changes might decrease the inhibitory activity of the mutated receptor.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, the clinical manifestation and severity of PHPT vary markedly. The variation in PHPT presentation has been reported to be associated with genetic variation of the vitamin D receptor, estrogen receptor, PTH, and calcium-sensing receptor (CASR) (1,2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, male gender and a young age at the time of diagnosis of primary hyperparathyroidism provide additional risks for the development of renal stones (8). Although hypercalciuria (9), increased plasma 1,25-dihydroxyvitamin D levels (10) and polymorphism in the calcium-sensing receptor (11) have been proposed as causes of the development of nephrolithiasis, the precise relationship between primary hyperparathyroidism and nephrolithiasis remains unclear (8). Computed tomography is the radiographic test of choice for diagnosis, with parenchymal calcifications being pathognomonic.…”
Section: Discussionmentioning
confidence: 99%